Abordagem participativa na elicitação de requisitos em ambientes virtuais para aprendizes surdos - Luz, Héllen Souza (Universidade Federal do Tocantins, 2022)
This study aims to elicit a set of requirements for a Virtual Learning Environment that guarantees the understanding and consideration of the deaf culture from the methodological approaches used by the deaf person who was the protagonist of the process. Secondly, this work presents in detail the use of focus groups in the process of elicitation of software requirements and a social science approach, the analysis of thematic-categorial content, to analyze the data resulting from the focus groups guarantee the necessary robustness to the process of software engineering. To do so, it develops an action research that begins in a review of integrative literature that allowed to gather systematically researched references to other relevant material for the state of the art about the design of web environments aimed at the deaf public. It then investigates the needs of the deaf in relation to the use of web environments to support the learning process through Focal Groups and Participatory Design Offices. Finally, it elaborates a catalog of requirements for web-based learning environments focused on the deaf based on comparative analysis of the data obtained in the theoretical framework, the focus groups and the participatory design workshop. The research made it possible to verify that, despite the existence of accessibility standards and the constitutional guarantees directed to the deaf people, much needs to be done so that their inclusion in school and digital informational environments is guaranteed. This delay may be related to the methodological approaches used to understand and teach the difference of the deaf over time. Thus, the understanding and consideration of the deaf culture can be considered the driving force of the other solutions addressed to the inclusion and care of the deaf in the different environments. This understanding must permeate the initiatives of developers, designers, teachers, content developers so that the deaf is effectively served.